Local residents' immediate responses to the 2018 Indonesia earthquake and tsunami. Issue 4 (November 2022) - Wang, Haizhong; Lindell, Michael K; Siam, Mohammad Rayeedul Kalam; Chen, Chen; Husein, Rahmawati
This study analyzes 488 household residents' responses to the 2018 Indonesia M7.5 earthquake and tsunami. Comparison of this event with past earthquake and tsunami events, such as the 2009 Samoa (M8.1), 2011 Christchurch (M6.3), and 2011 Tohoku (M9.0) events, identifies commonalities and differences among people's responses to these events. The results show that many Palu respondents failed to recognize strong earthquake ground motion as an environmental cue to a tsunami, but this was partially offset by an informal peer warning network. Most of the warnings only mentioned one of the six recommended message elements—the tsunami hazard. However, this brief message might have been adequate for many people if they could infer the certainty, severity, and immediacy of the threat, and appropriate evacuation modes, routes, and destinations. Unlike two comparison cases, some Palu respondents actually began their evacuation later than they expected the tsunami to strike. This might be due to spending too much time milling (seeking additional information, relaying warnings, reuniting families, and preparing to evacuate)—given the tsunami's extremely rapid onset. This finding underscores the need for coastal emergency managers to promote evacuation preparedness for near-field tsunamis in which households pack Grab and Go kits in advance, warn others while evacuating, and plan in advance where to reunite household members who must evacuate separately.